Integration of HIRARC and B/C Ratio to Reduce the Number of Accidents in PT. XYZ - Valentino, Dedy Saputra; Pawitra, Theresia Amelia; Tosungku, La Ode Safar (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
PT XYZ is one of the companies engaged in the mining industry. The company has total coal reserves of 5.8 million tons and produces a coal calorific value of 4900 Kcal/kg GAR. PT XYZ uses a 30-ton class dump truck for overburdened transportation activities. Overburden transportation is transporting material from one location or facility to another. The operation of dump trucks has risks that need to be controlled to minimize work accidents. Truck operators have considerable risks, including bumping, hitting, slipping, falling, and pinched. This study aims to identify potential accidents that can occur and propose preventive measures based on the risk level of each possible accident in the operation of dump trucks using the HIRARC method at PT XYZ. Based on the results of the study shows that the potential hazards experienced by dump truck operators include collisions, pinching, slipping, overturning units, backing units when on an incline, buckets crashing into vessels, grazing other units, low back pain, neck pain, herniated nucleus pulposus, fatigue, loss of control, unprotected operators, collapsed and dragged units, reduced control, loss of control, trapped units, buried units, falling into ravines, damaged units. In addition, the risks experienced by dump truck operators are 6 high risks, 7 medium risks, and 9 low risks. From the overall transportation of overburden material, dump truck operators experienced a high risk of 27%, a medium risk of 32%, and a low risk of 41%.